Effects of nitrogen fertilizer on flour protein composition and dough quality in wheat cultivated in La Pampa province (Semiárida, 2020)
Breadmaking quality of wheat flour (Triticum aestivum L.) depends not only on the genotype but also on the availability of nitrogen, and wheat protein composition is important for understanding the biochemical basis of wheat quality. The objective of this study was to evaluate the effect of nitrogen availability on flour protein fractions, to analyze their distribution and relationship with bakery quality. We worked with ACA 315 cultivar, where different application rates and timing of nitrogen nutrition were tested. Flour protein fraction composition was quantified following two protocols. Nitrogen application affected glutenin concentration and protein fraction composition favoring polymeric proteins and increasing polymeric/monomeric proteins ratio, however, increase of flour polymeric proteins did not resulted in improved rheological properties. The nitrogen added in this experiment in the different experiments was not enough to obtain good quality bakery flours. Low protein values were obtained in grain, low gluten concentration and the dough had low W value and high P/L, being very tenacious and no very extensible. Due to low grain protein concentration farinograph parameters could not be interpreted since, under these conditions they are overestimated. These results show that not only genotypic genetic information, should be considered, also gene expression regulation in response to environmental factors, such as nitrogen availability. Therefore, genotype should continue to be studied, both at the level of variation allelic individual and in combination of different alleles of grain reserve proteins. It is also necessary to incorporate in future studies amount and timing of nitrogen application and other nutrients, such us S, in order to obtain better quality bakery flours in La Pampa province.
Keywords: glutenins; gliadins; dough rheological properties